Two phase simulation and sensitivity analysis of effective parameters on turbulent combined heat transfer and pressure drop in a solar heat exchanger filled with nanofluid by Response Surface Methodology. (15th August 2016) - Mamourian, Mojtaba; Milani Shirvan, Kamel; Mirzakhanlari, Soroush
Abstract: In this paper, a 2-D numerical investigation and a sensitivity analysis of combined turbulent mixed convection and radiation heat transfer have been done using two phase mixture model in a solar heat exchanger. Numerical simulations are carried out to study the effects of the four parameters, the Richardson number (10 −2  ≤ Ri ≤ 10 2 ), volume fraction of nanoparticles (0.00 ≤ ϕ ≤ 0.04), nanoparticles diameter (40 nm ≤ dp  ≤ 60 nm) and the wall surface emissivity (0 ≤ ε ≤ 1). The effective parameters analysis is processed utilizing the RSM (Response Surface Methodology). It is found that decreasing the Ri number and ϕ and also increasing in ε and dp increases the mean total Nusselt number. Due to a decrease in Ri number and increase in ϕ, ε and dp the pressure drop ratio enhances. The sensitivity of the mean total Nusselt number and pressure drop ratio to Ri number is negative. The sensitivity of the mean total Nusselt number to dp and ε is positive but to ϕ is negative. Moreover, the sensitivity of the mean Nusselt number to Ri number, ϕ, dp and ε is more than the sensitivity of the pressure drop ratio to these parameters. Highlights: The optimum conditions for better heat transfer and least pressure drop are studied. An analysis is performed using the RSM (Response Surface Methodology). The mean Nusselt number and pressure drop sensitivity to Ri number is negative. The pressure drop sensitivity to Ф and dp is positive. The Nusselt number is more sensitive to Ri number rather than the pressure drop.